Prosthetic rehabilitation of a maxillary defect caused by ameloblastoma of rare occurrence: A clinical case report - Harini Kallathappa Shivakumar; Sounyala Rayannavar; Deepa Suraj Chougule; Smitha Sharan (Wolters Kluwer Medknow Publications, 2020)
According to WHO statistics, individuals of the Indian subcontinent have the highest prevalence of orofacial cancer. Surgery, radiation, chemotherapy, or combination therapies are commonly administered treatment modalities for the treatment of oral cancer. Rehabilitation after surgical resection of the maxillary area is often a challenging task for maxillofacial prosthodontists. The size and location of the defect usually influence the amount of impairment and difficulty in prosthetic rehabilitation. Communication between nasal and oral cavities causes difficulty in swallowing and speech and gives unesthetic appearance. Obturator prosthesis is commonly used as an effective means for rehabilitating hemimaxillectomy cases. This article presents a case of acquired maxillary defect due to ameloblastoma with unfavorable undercuts, which was successfully treated by an immediate obturator following surgical resection and followed by a one-piece closed hollow bulb obturator, by utilizing the remaining palate and dentition to maximize the support, stability, and retention, which acts as a barrier to the communication between the oral and nasal cavities.